DEVELOPMENT AND VALIDATION OF AN ANALYTICAL METHOD FOR THE SIMULTANEOUS DETERMINATION OF IMEGLIMIN HYDROCHLORIDE AND SITAGLIPTIN PHOSPHATE USING REVERSE-PHASE HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY - VIJAY AGRAWAL; KOMAL PATEL; RAJESH VARADE (Asian Journal of Pharmaceutical and Clinical Research, 2026)
Objectives: The aim of the study was to develop and validate a precise reverse-phase high-performance liquid chromatography (RP-HPLC) method for concurrent estimation of imeglimin hydrochloride (IMG) and Sitagliptin phosphate (SIT) in bulk and dosage forms as per International Council for Harmonization guidelines. Methods: The RP-HPLC technique utilized a Fortis C18 column (100×4.6 mm, 2.5 μm) with a mobile phase consisting of methanol and water, along with 0.1% ortho phosphoric acid in a 43:57 ratio at pH 3.5 for the separation of IMG and SIT. The chromatographic parameters included a flow rate of 0.7 mL/min and an injection volume of 20 µL, with a brief run time under isocratic conditions. Detection was carried out using a diode array detector, and quantification was performed at 266 nm. Results: The RP-HPLC method exhibited outstanding linearity, with R2 values of 0.9995 for IMG and 0.9996 for SIT at 266 nm. The recovery rates were determined to be 99.61–101.23% for IMG and 99.27–102.48% for SIT. The limits of detection (LOD) and limit of quantification (LOQ) for IMG were established at 0.450 ppm and 1.365 ppm, respectively. For SIT, the LOD and LOQ were found to be 0.028 ppm and 0.086 ppm, respectively. Conclusion: The method developed in this research is accurate, robust, and offers excellent separation and resolution of IMG and SIT. The findings support the potential use of this method for quality control of combination formulations.